2017
DOI: 10.3390/md15040087
|View full text |Cite
|
Sign up to set email alerts
|

Marine Cyclic Guanidine Alkaloids Monanchomycalin B and Urupocidin A Act as Inhibitors of TRPV1, TRPV2 and TRPV3, but not TRPA1 Receptors

Abstract: Abstract:Marine sponges contain a variety of low-molecular-weight compounds including guanidine alkaloids possessing different biological activities. Monanchomycalin B and urupocidin A were isolated from the marine sponge Monanchora pulchra. We found that they act as inhibitors of the TRPV1, TRPV2, and TRPV3 channels, but are inactive against the TRPA1 receptor. Monanchomycalin B is the most active among all published marine alkaloids (EC 50 6.02, 2.84, and 3.25 µM for TRPV1, TRPV2, and TRPV3, correspondingly)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
(82 reference statements)
0
17
0
Order By: Relevance
“…All tests on expressed channels were performed according to previously described standard protocols. Testing for receptors rTRPV1, mTRPV2, hTRPV3, rTRPA1, stably expressed in CHO cells, was carried out using the calcium imaging method as described [ 64 ]. The maximal tested concentration of peptide was 1 μM.…”
Section: Methodsmentioning
confidence: 99%
“…All tests on expressed channels were performed according to previously described standard protocols. Testing for receptors rTRPV1, mTRPV2, hTRPV3, rTRPA1, stably expressed in CHO cells, was carried out using the calcium imaging method as described [ 64 ]. The maximal tested concentration of peptide was 1 μM.…”
Section: Methodsmentioning
confidence: 99%
“…Following bioassay-guided fractionation of the most active sponge Monanchora viridis , we isolated crambescidin 800 (C800), a guanidine alkaloid, as an active compound against TNBC cells. Guanidine alkaloids from sponges of genus Monanchora are reported to have diverse chemical structures and biological activities [ 21 , 22 , 23 , 24 ], which includes inducing cytotoxic activities [ 25 , 26 ] and apoptosis against leukemia cells [ 25 , 27 ], overcoming drug resistance by induction of autophagy and lysosomal membrane permeabilisation in urogenital cancer cells [ 28 ], and inhibiting HIV-1 fusion [ 29 ], transient receptors potential channels [ 30 ], and EGF-induced neoplastic transformation in cancer cells [ 31 ]. It was also reported that the alteration of the compound’s structure affected its cytotoxic activities, inducing apoptosis, cell cycle progression, and the induction of signaling pathways in cancer cells [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…panicea polyacetylene isopetrosynol ( 284 ) [ 306 ]; cyanobacterium Leptolyngbya sp. macrolide polyketide leptolyngbyolide B ( 285 ) [ 307 ]; ascidian Lissoclinum mandelai macrocyclic polyketide mandelalide C ( 286 ) [ 308 ]; sponge Hyrtios digitatus tetracyclic merosesquiterpene 19-methoxy-9,15-ene-puupehenol ( 287 ) [ 309 ]; sponge Monanchora pulchra cyclic guanidine alkaloid monanchomycalin B ( 288 ) [ 310 ]; sponge Plakortis simplex polyketide monotriajaponide A ( 289 ) [ 311 ]; sponge Mycale lissochela terpenoid mycalenitrile-15 ( 290 ) [ 312 ]; sponge Hyrtios sp. meroterpenoid nakijinol G ( 291 ) [ 313 ]; sponge Theonella swinhoei cyclic pentapeptide nazumazole D ( 292 ) [ 314 ]; fungus Aspergillus sp.…”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%